Mergers & Acquisitions for Dummies - Snow, Bill (Ascent Audio, 2019)
Are you a business owner or executive thinking about selling a division, a subsidiary, or the entire company? Or are you thinking about how you may be able to grow your business by merging with or acquiring other companies? Or are you a student thinking about making a career in a mergers and acquisitions (M&A) related industry? In other words, if you are looking for a plain-language, no-nonsense guide about how mergers and acquisitions can affect your company and career, you've found your book! Mergers & Acquisitions for Dummies is your insider's handbook about the practice of buying and selling companies. It explains the entire M&A process step by step, introduces you to industry specific terms and acronyms, details the documents used when buying or selling a company, discusses valuation techniques, reveals insights about how to finance deals, provides real world examples of how to structure transactions and bridge valuation gaps between Buyer and Seller, and gives you the basic tools you will need to successfully close M&A transactions. Plus, you'll get expert advice on identifying and contacting potential M&A targets, performing due diligence, drafting the purchase agreement, and integrating new employees after the deal closes.